Lung Ultrasound Signs and Their Correlation With Clinical Symptoms in COVID-19 Pregnant Women: The “PINK-CO” Observational Study - Vetrugno, Luigi; Sala, Alessia; Orso, Daniele; Meroi, Francesco; Fabbro, Sebastiano; Boero, Enrico; Valent, Francesca; Cammarota, Gianmaria; Restaino, Stefano; Vizzielli, Giuseppe; Girometti, Rossano; Merelli, Maria; et al. (Frontiers in Medicine, 2022)
Objective: Analyze the application of lung ultrasound (LUS) diagnostic approach in obstetric patients with SARS-CoV-2 infection and compare LUS score and patients’ symptoms. Design: a single-center observational retrospective study from 31 October 2020 to 31 March 2021. Setting: Department of Ob/Gyn at the University-Hospital of Udine, Italy. Participants: pregnant women with SARS-CoV-2 diagnosed with reverse transcription-polymerase chain reaction (RT-PCR) swab test, subdivided as symptomatic and asymptomatic COVID-19 patients. Exposure: LUS evaluation both through initial evaluation upon admission and through serial evaluations. Main outcome: reporting LUS findings and LUS score characteristics. Results: Symptomatic COVID-19 patients showed a higher LUS (median 3.5 vs. 0, p-value <0.001). LUS was significantly correlated with COVID-19 biomarkers as CPR (p=0.011), interleukin-6 (p=0.013) and pro-adrenomedullin (p-value=0.02), and inversely related to arterial oxygen saturation (p-value=0.004). The most frequent ultrasound findings were focal B lines (14 vs. 2) and the light beam (9 vs. 0). Conclusion: Lung ultrasound can help manage pregnant women with SARS-CoV-2 infection during a pandemic surge.